2017
DOI: 10.1016/j.actamat.2017.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation of the Kirkendall marker plane and the role of Ni and other impurities on the growth of Kirkendall voids in the Cu–Sn system

Abstract: The presence of bifurcation of the Kirkendall marker plane, a very special phenomenon discovered recently, is found in a technologically important Cu-Sn system. It was predicted based on estimated diffusion coefficients; however, could not be detected following the conventional inert marker experiments. As reported in this study, we could detect the locations of these planes based on the microstructural features examined in SEM and TEM. This strengthens the concept of the physico-chemical approach that relates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…It should be noted here that a different value of this ratio was reported in Ref. [16], which was an average of data estimated at different locations in different diffusion couples, compared to the data reported in this study estimated based on the micrograph, as shown in Figure 4a.…”
Section: Integrated Interdiffusion Coefficientcontrasting
confidence: 64%
See 1 more Smart Citation
“…It should be noted here that a different value of this ratio was reported in Ref. [16], which was an average of data estimated at different locations in different diffusion couples, compared to the data reported in this study estimated based on the micrograph, as shown in Figure 4a.…”
Section: Integrated Interdiffusion Coefficientcontrasting
confidence: 64%
“…Now we compare the efficiencies and difficulties of estimation of the data utilizing the growth of the product phases, as shown in Figure 4a, in the Cu-Sn system. The Cu/Sn diffusion couple was annealed at 200 °C for 81 hrs (i.e., 2 = 2×81×3600 s) in which two phases Cu3Sn and Cu6Sn5 grows in the interdiffusion zone [16]. The average thicknesses of the phases are estimated as 3.5 m (= ∆ 3 ) for Cu3Sn and 13 m (= ∆ 6 5 ) for Cu6Sn5.…”
Section: Integrated Interdiffusion Coefficientmentioning
confidence: 99%
“…As will be shown by the next set of figures, this contrast corresponds to porosity in the material, which may be on the surface and/or internal. We argue that these are Kirkendall‐type of voids, associated with asymmetric diffusional flux of elements out of the cathode.…”
Section: Resultsmentioning
confidence: 87%
“…This means that bifurcation of the initial Kirkendall plane will occur and each phase should have its own Kirkendall plane Kε and Kη', which has also been experimentally observed. 21 Kirkendall planes have been shown to be stable or unstable. If a trace marker experiment results in a line of markers this indicates a stable Kirkendall plane, however if markers are distributed throughout a phase it is unstable.…”
Section: Cumentioning
confidence: 99%